Unveiling the hidden threat: investigating gastrointestinal parasites and their costly impact on slaughtered livestock - Hafiz Muhammad Rizwan; Hafiz Muhammad Zohaib; Muhammad Sohail Sajid; Urfa Bin Tahir; Razia Kausar; Nadia Nazish; Mourad Ben Said; Nimra Anwar; Mahvish Maqbool; Dalia Fouad; Farid Shokry Ataya (Revista Brasileira de Parasitologia Veterinária, 2024)
Abstract This study investigated the prevalence of gastrointestinal (GI) parasites in ruminants slaughtered at the abattoir in district Narowal, Punjab, Pakistan. The overall prevalence of parasitic infection was determined to be 72.92% based on faecal examination. Among the ruminant species, goats exhibited a significantly higher (P < 0.05) prevalence of parasitic infection (78.63%) compared to cattle, buffalo, and sheep. Additionally, female ruminants showed a significantly higher (P<0.05) prevalence of infection (85.62%) compared to males (65.13%). The intestines (both small and large) of small and large ruminants were found to be significantly more affected, with a prevalence of 39.58% of parasitic infection compared to other examined organs. A total of ten parasitic genera were identified in ruminants, including hydatid cysts. Ruminants with a high burden of parasites (45.74%) significantly outnumbered those with light (23.40%) and moderate (30.85%) burdens. Economically, the estimated annual losses in Pakistan due to organ condemnation with GI parasites were substantial, amounting to Pak. Rs. 405.09/- million (USD = 1,428,760). These findings underscore the significance of GI parasite infections as a major animal health concern and a cause of significant economic losses in the research area.